2014
DOI: 10.4293/108680813x13693422521007
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Adnexal Masses in Pregnancy

Abstract: Surgical management of adnexal masses during pregnancy appears to have favorable outcomes for both mother and fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 12 publications
2
48
0
1
Order By: Relevance
“…The mean age of study participants ranged from 25.4 to 31.6 years. All study participants had undergone surgery during the second trimester of pregnancy except for one woman who underwent surgery at 11 weeks of pregnancy owing to suspicion of malignancy . There were six patients from three studies in whom laparoscopic surgery was unsuccessful, necessitating conversion to open surgery; these patients were considered to be part of the laparotomy‐treatment cohort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of study participants ranged from 25.4 to 31.6 years. All study participants had undergone surgery during the second trimester of pregnancy except for one woman who underwent surgery at 11 weeks of pregnancy owing to suspicion of malignancy . There were six patients from three studies in whom laparoscopic surgery was unsuccessful, necessitating conversion to open surgery; these patients were considered to be part of the laparotomy‐treatment cohort.…”
Section: Resultsmentioning
confidence: 99%
“…There were six patients from three studies in whom laparoscopic surgery was unsuccessful, necessitating conversion to open surgery; these patients were considered to be part of the laparotomy‐treatment cohort. Of these individuals, one patient had a cystic teratoma that could not be elevated out of the pelvis without risk of rupture, and the other five patients had a mass that was too densely adhered to the pelvis to permit exposure in the operative field . Cystectomy was performed in 111 patients in the laparoscopy group and 106 patients in the laparotomy group; one woman in the laparoscopy group underwent adnexectomy and all other patients underwent oophorectomy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 They concluded that surgical management of adnexal masses during pregnancy appears to have favourable outcomes for the mother and the fetus. There was no significant difference in obstetric outcomes between the laparoscopy and laparotomy groups.…”
Section: Discussionmentioning
confidence: 99%
“…A single cyst measuring less than 10 cm, one side, and without ascites can be left to 18 weeks without further medication; however, if the cyst persistently increases in size, surgical exploration is required. For mixed cysts larger than 5 cm, bilateral sides, or with nipple should be followed up with ultrasound; if it persists or the size increases by 30%–50%, surgical exploration is required 2,11,12. It has been reported that cysts larger than 15 cm are 12 times more likely to be malignant than cysts less than 6 cm in diameter 13.…”
Section: Discussionmentioning
confidence: 99%